Comparison of mechanical stability of modified pedicle screw fixator and unilateral lumbopelvic fixation for treating sacroiliac joint disruption: A finite element analysis study - Jun Zhang; Yan Wei; Baoqing Yu; JianWang; Weizhong Yin (Acta Orthopaedica et Traumatologica Turcica, 2024)
Objective: This study aimed to investigate the mechanical stability of a modified pedicle screw fixator and compare it with unilateral lumbopelvic fixation for treating sacroiliac joint disruption using finite element simulation technology.